Heart work: Indigenous doulas responding to challenges of western systems and revitalizing Indigenous birthing care in Canada - Caroline Fidan Tyler Doenmez; Jaime Cidro; Stephanie Sinclair; Ashley Hayward; Larissa Wodtke; Alexandra Nychuk (BMC, 2022)
Abstract Background In Canada, there has been a significant increase in the training of Indigenous doulas, who provide continuous, culturally appropriate support to Indigenous birthing people during pregnancy, birth, and the postpartum period. The purpose of our project was to interview Indigenous doulas across Canada in order to document how they worked through the logistics of providing doula care and to discern their main challenges and innovations. Population/setting Our paper analyzes interviews conducted with members of five Indigenous doula collectives across Canada, from the provinces of British Columbia, Manitoba, Ontario, Quebec and Nova Scotia. Methods Semi-structured interviews were conducted with members of the five Indigenous doula collectives across Canada in 2020 as part of the project, "She Walks With Me: Supporting Urban Indigenous Expectant Mothers Through Culturally Based Doulas." Interview transcripts were approved by participants and subsequently coded by the entire research team to identify key themes. Results Our paper examines two themes that emerged in interviews: the main challenges Indigenous doulas describe confronting when working within western systems, and how they navigate and overcome these obstacles. Specifically, interview participants described tensions with the biomedical approach to maternal healthcare and conflicts with the practice of Indigenous infant apprehension. In response to these challenges, Indigenous doulas are working to develop Indigenous-specific doula training curricula, engaging in collective problem-solving, and advocating for the reformation of a grant program in order to fund more Indigenous doulas. Conclusions Both the biomedical model of maternal healthcare and the crisis of Indigenous infant apprehension renders Canadian hospitals unsafe and uncomfortable spaces for many Indigenous birthing people and their families. Indigenous doulas are continually navigating these challenges and creatively and concertedly working towards the revitalization of Indigenous birthing care. Indigenous doula care is critical to counter systemic, colonial barriers and issues that disproportionately impact Indigenous families, as well as recentering birth as the foundation of Indigenous sovereignty and community health.